EFFECTIVENESS OF ASTHMA SELF-MANAGEMENT EDUCATION (ASME) ON IMPROVING THE QUALITY OF LIFE: A LITERATURE REVIEW - Novarika Aliya Rizky; Arista Maisyaroh; Dwi Ochta Fibrianti; Syaifuddin Kurnianto; Eko Prasetya Widianto (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Asthma is a common chronic respiratory disease that affects around 300 million people of all ages worldwide so that it has an impact on patients both physically, activity restrictions, and psychosocially, in terms of quality of life. Objective: This study aims to assess the effectiveness of Asthma Self Management Education (ASME) to improve the quality of life of people with asthma. Design: The design of this study uses a literature review. Data Sources: Initial searches of journal articles were performed on the Pubmed, Science Direct, and Google Schollar search databases from 2017-2021 with the keyword Asthma self management education. The ASME study found 807 articles but only 7 journal articles that met the search inclusion criteria. Review Methods: A literature review procedures were used to collect library data, reading and taking notes, as well as critical assessment of managing research materials Results: According to the results of the literature review, ASME has several variants with an average duration of ASME being carried out for 6 months to 15 months. Asthma control is measured to assess lung function and behavioral changes in individuals with asthma. The ASME technique is effective as an educational method in improving lung function, asthma control, quality of life, and behavior change which are important components of asthma sufferers. Conclusion: The application of ASME technical interventions to asthma sufferers can be used as an educational program to improve behavior changes that can control asthma symptoms non-pharmacologically